Characterization of Unique Serials Indexed in the Zoological Record. - Janet A. Hughes (Issues in Science and Technology Librarianship, 2001)
A study was conducted to characterize the sources of references found in ZR that are not found in BIOSIS Previews. Zoological Record (ZR), published jointly by the Zoological Society of London and BIOSIS, is the authoritative and most comprehensive source of zoological information (Zoological Record web page 1998). It covers nearly 6,000 international journals, review annuals, newsletters, popular magazines, monographs, meeting proceedings, books and reports. Despite the seemingly ample coverage of biological information, some Penn State zoologists feel that the cancellation of ZR in 1995 deprived them of access to much of their literature. The characterization of the unique references is necessary to fully understand the value of such references to a comprehensive literature search.